Notes on the genus Pellis Sheng & Sun, 2014 (Hymenoptera, Ichneumonidae, Banchinae), with a new record from Japan - Watanabe, Kyohei (Zootaxa, 2020)
The genus Pellis Sheng & Sun, 2014 is newly recorded from Japan based on a Chinese species, P. acarinata Sheng & Sun, 2014, collected from Honshu. Both the genus and species are redescribed based on the data of original description and Japanese materials.A key to Asian genera of Atrophini is also proposed.